BADAN USAHA MILIK DESA SEBAGAI PEMBERDAYAAN EKONOMI (SYARIAH) MELALUI ORGANISASI BERBASIS KEAGAMAAN (ISLAM) - Dauri; Ricco Andreas (Legalita, 2019)
This study aims to examine and provide new concepts in the development of Village-Owned Enterprises (BUMDes) through religious organizations, especially Islam. BUMDes is one of the economic institutions operating in rural areas that must have differences with economic institutions in general. This is intended so that the existence and performance of BUMDes can contribute significantly to improving the welfare and economic prosperity of the community, the majority of the population of Indonesia are Muslims, so that BUMDes are in accordance with Islamic contracts. The problems that will be discussed in this study are 1. What is the development of Village-Owned Enterprises as Economic Empowerment (sharia) through the current Religious Based Organization (Islam). 2. What is the concept in the development of Village-Owned Business Entities Through Religious (Islamic) Based Organizations. This research method uses a normative juridical system by studying library materials and documents related to the development of BUMDes. This study shows that existing contracts in Islamic economics can be implemented on BUMDes in accordance with laws and regulations. In addition to having strengths and opportunities, this concept also has disadvantages and threats. To realize Islamic economy-based BUMDes this requires an active role and joint commitment from the village government, the community, Fatayat Nahdatul Ulama (NU), Muslimat, and other Islamic organizations that will develop Islamic economics, so that the needs of al-dharuriyah (primary), al-hajiyyah ( secondary), al-thsaniyyah (complementary) in the village.